The Redox Balance in Erythrocytes, Plasma, and Periosteum of Patients with Titanium Fixation of the Jaw - Borys, Jan; Maciejczyk, Mateusz; Krȩtowski, Adam J.; Antonowicz, Bozena; Ratajczak-Wrona, Wioletta; Jabłońska, Ewa; Załęski, Piotr; Waszkiel, Danuta; Ładny, Jerzy R.; Żukowski, Piotr; Zalewska, Anna (Frontiers in Physiology, 2017)
Titanium miniplates and screws are commonly used for fixation of fractured or osteotomised jaws. Despite the opinion of their biocompatibility, in clinical practice symptoms of chronic inflammation around the fixation develop in some patients, even many years after the application of miniplates and screws. The cause of these complications is still an open question. Taking into account that oxidative stress is one of the toxic action of titanium, we have evaluated the antioxidant barrier as well as oxidative stress in the erythrocytes, plasma and periosteum covering the titanium fixation of the jaws. The study group was composed of 32 patients aged 20–30 with inserted miniplates and screws. Antioxidant defence: catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase-1 (SOD1), uric acid (UA), total antioxidant capacity (TAC), as well as oxidative damage products: advanced oxidation protein products (AOPP), advanced glycation end products (AGE), dityrosine, kynurenine, N-formylkynurenine, tryptophan, malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), total oxidant status (TOS), and oxidative status index (OSI) were evaluated. SOD1 activity (↓37%), and tryptophan levels (↓34%) showed a significant decrease while AOPP (↑25%), TOS (↑80%) and OSI (↑101%) were significantly elevated in maxillary periosteum of patients who underwent bimaxillary osteotomies as compared to the control group. SOD-1 (↓55%), TAC (↓58.6%), AGE (↓60%) and N-formylkynurenine (↓34%) was statistically reduced while AOPP (↑38%), MDA (↑29%), 4-HNE (↑114%), TOS (↑99%) and OSI (↑381%) were significantly higher in the mandibular periosteum covering miniplates/screw compared with the control tissues. There were no correlations between antioxidants and oxidative stress markers in the periosteum of all patients and the blood. As exposure to the Ti6Al4V titanium alloy leads to disturbances of redox balance in the periosteum surrounding titanium implants of the maxilla and the mandible so antioxidant supplementation should be recommended to the patients undergoing treatment of dentofacial deformities with the use of titanium implants. The results we obtained may also indicate a need to improve the quality of titanium jaw fixations through increase of TiO2 passivation layer thickness or to develop new, the most highly biodegradable materials for their production.